Clinicopathological study of endometrial polyps: experience from a tertiary care center - Alyea Al-Harthy; Mohammad Arafa (Folia Medica)
Introduction: An endometrial polyp (EP) is an abnormal growth of the endometrium inside the uterine cavity. Histologically, the polyp contains glandular, stromal, vascular (thick-walled vessels), and connective tissue elements (fibrous stroma). The most common symptoms of patients with endometrial polyps are abnormal bleeding and infertility. Aim: To assess cases of endometrial polyps received at the pathology department of a hospital by exploring the different presentations of the patients and the correlation with the clinico-pathological features. Materials and methods: This retrospective, cross-sectional study used patient data from January 2018 to December 2022. It was conducted in the pathology department of a tertiary care center. It included 180 women with endometrial polyps. Data were collected from the hospital information system’s medical records, and the Statistical Package for the Social Sciences (SPSS), version 26.0, was used to analyze the data. Results: The patients’ ages ranged from 29 to 88 years. About one-third of the patients were aged between 30 and 40 years. Patients with a single polyp were more than those with multiple polyps. Abnormal bleeding and infertility were the most prevalent symptoms. All the cases were histopathologically benign except for one who presented with malignancy. Age did not show significant association with recurrence. In more than 75% of patients, there was a consensus between the clinical assessments and pathology results. Conclusion: Most endometrial polyps are benign and single with a good concordance between the clinical suspicion and the histopathological confirmation.